Novelties in Vos Estis Lux Mundi 2023 - Thomas, Domy (Iustitia, 2024)
Through this article, the author aims to point out the changes presented in Vos estis lux mundi 2023 comparedwith the previous version Vos estis lux mundi 2019. After a brief explanation ofthe purpose of the revision, the two titles of the new document and its modified articles are examined in comparison with the old document, and the changes and novelties in the new document are highlighted.